SISTEM PENDUKUNG KEPUTUSAN UNTUK KESESUAIAN LAHAN DAN TANAMAN PERTANIAN MENGGUNAKAN METODE PROFILE MATCHING - Minarwati (Jurnal Informatika Komputer, Bisnis dan Manajemen, 2021)
This study was made based on the body's requirements matching, because during this banya land cultivation cases that do not fit resulting in crop failures or even crop failure. The data used agricultural plant data consisting of rice, corn, soybeans and wheat. The right decision related to tersebuat is one of the determining factors in improving the agricultural sector. Determination of the appropriate plant based agriculture through three criteria: soil, climate and topography. Climate criteria has 4 sub-criteria which consists of precipitation, temperature, pH, and the intensity of the irradiation. This study shows how a decision support system profile matching can emberika recommendations on priorities for the agricultural crops of the land. In a profile matching methods are steps include finding the difference / gap, gap weighting, determine and calculate the value of core and secondary factor, calculate totals and calculates the ranking of land as a result. Interpolation calculations are also used in this system, which is to help find the value for the data used in the form of intervals. Interpolation is also used to help locate the weight values ​​gap gapnya values ​​in decimal form. From the results of this study demonstrate the benefits of the profile matching method as a model for decision support system that can help fatherly determine the appropriate agricultural crops occur ring on one particular area.